Sport governance - Russell Hoye (Elsevier, 2024)
Sport Governance provides a comprehensive guide to the practical application of governance principles to amateur and professional sport organisations operating at the community, state/provincial, national, and international levels. It presents a balanced view between accepted practice and what contemporary research evidence tells us about a range of governance principles and practices.